Expression analysis of cannabinoid receptors 1 and 2 in B cells during pregnancy and their role on cytokine production. (August 2016) - Wolfson, M.L.; Muzzio, D.O.; Ehrhardt, J.; Franchi, A.M.; Zygmunt, M.; Jensen, F.
Highlights: Cannabinoid receptor 1 (CB1) and 2 (CB2) are highly expressed on B cells. CB1 and CB2 expression on B cells is strongly modified during pregnancy. CB1 and CB2 activation in B cells during pregnancy provoke a differential response in term of cytokine production. Abstract: The endocannabinoid system consists in a family of lipids that binds to and activates cannabinoid receptors. There are two receptors so far described, the cannabinoid receptor 1 (CB1) and 2 (CB2). In the context of pregnancy, the endocannabinoid system was shown participates in different key aspects of reproductive events. B-lymphocytes are pleiotropic cells belonging to the adaptive arm of the immune system. Besides immunoglobulin production, B-lymphocytes were recently shown to be actively involved in antigen presentation as well as cytokine production, thus playing a central role in immunity. In this study we first aimed to characterize the expression of CB1 and CB2 receptors in B cells during pregnancy and then analyze the impact of their activation in term of cytokine production by B cells from pregnant and non-pregnant mice. We observed that the expression of CB1 and CB2 receptors in B-lymphocytes is differentially regulated during pregnancy. While CB2 expression is down regulated CB1 is augmented in B-lymphocytes of pregnant mice. Additionally, the treatment of activated B-lymphocytes with specific CB1 and CB2 agonists, showed a different response in term of cytokine production. Particularly, CB1 against boosted the production of the anti-inflammatory cytokine IL-10 by activated B-lymphocytes from pregnant mice.